Simulation of saturable absorber material length effect on characteristics of Passive Q-switching and Stokes pulses - Salih, Abdul-Kareem Mahdi; Hassan , Ghofran Zamel (University of Thi-Qar Journal, 2019)
The effect of saturable absorber material length on characteristics of passive Q-switching and Stokes pulses has been simulated. A software computer program has been based for solving a rate equations model numerically by Rung –Kutta- Fehalberg method. (Nd:GdVO4), (Cr+4:YAG), and Ba(NO3)2 are used as a active medium, saturable absorber material, and Raman medium respectively. The study shows that an decrease in pulse duration for both pulses (passive Q- switching and Stocks) with saturable absorber material length increases. While the energy and the power are increase with saturable absorber material length increases.